Effect of zinc supplementation from organic and inorganic sources on performance, nutrient utilization and carcass characteristics in lambs - NAGALAKSHMI, D; HIMABINDU, D (The Indian Journal of Animal Sciences, 2013)
An experiment was conducted on 42 male Nellore lambs to determine the effect of zinc level and source on performance, nutrient digestibility and carcass characteristics of lambs by randomly allotting them to 7 groups in completely randomized design. The dietary treatments were, viz. basal diet (no Zn supplementation, BD; 29.3ppm); other 6 groups were offered BD supplemented with 15, 30 or 45ppm Zn from Zn sulphate and Zn proteinate, respectively. The lambs were fed the respective diets at 3.5% body weight to meet nutrient requirements except Zn for 150 days including 6-day metabolic trial. The intake and digestibility of organic nutrients including fibre fractions, nitrogen and energy balances were similar among BD and Zn supplemented lambs at varying doses and sources. The dose and source of Zn had no effect on weight gains, nutrient intake and efficiency. The pre slaughter weight, hot carcass weight, dressing percentage, edible and non-edible proportion of carcass and yield of whole sale cuts were similar among the groups except for higher rack yield on 30 and 45ppm Zn supplementation. Meat yield was higher and fat yield was lower in ZnSO4 fed lambs compared to Zn proteinate. The proportion of meat per unit of bone was higher in Zn supplemented lambs. The results indicated that 29.3ppm Zn in diets, meeting the NRC (1985) recommendations was sufficient for maximum performance and carcass traits in lambs. Dose and source of Zn supplementation influenced bone, meat and fat proportions in carcass.